THE WAR MEMORIAL OF CONSTANTINE FACING RISKS AND VULNERABILITY. (Journal of Sciences & Technology, 2019)
The war memorial of Constantine is in a state of advanced degradation; despite its major importance, the monument and its surroundings are facing devastating factors that alter both its invaluable values and authenticity. So, what are the main factors that caused this degradation? Initially, the degradations noticed are due to a set of risks. The in situ survey conducted as well as the comparative study confirmed the presence of risks on the site through the identification of nine natural and anthropogenic hazards. Furthermore, the cross-examination of the data obtained from the subsequent studies showed that the damage of the risks influenced the monument in two forms: physical and functional. In conclusion, the effect of the damage increased the degree of vulnerability of the monument.